Scala naturae: the impact of historical values on current 'evolution of language' discourse. Issue 1 (23rd September 2017) - Ullrich, Robert; Mittelbach, Moritz; Liebal, Katja
Abstract: Various complaints about the consistent use of a non-epistemological 'norm of progress' (also known as 'Scala Naturae') can be found frequently in recent evolution of language and communication literature. Affiliated to earlier studies that addressed quantification of some overt indicators such as word combinations of 'high + species', the current account aims to go beyond the obvious in describing the presumed phenomena. Using a mixed-methodology approach, we quantify the general use of vocabulary, range of study species, amount of 'progressionist attributes' and subsequently qualify the context of some key words. Investigating 915 peer-reviewed articles from a species-comparative evolution of language and communication discourse, we found that articles focussing on species groups historically regarded as 'high' make more use of attributes implying directed progress than otherwise. We subdivided all articles in two distinct corpora. Articles using the term 'language' or 'speech' in title, abstract or keywords were labelled 'language'. Those using other terms than language were labelled 'communication'. We could identify a more diverse focus on studied species groups and a more behaviouristic vocabulary in corpus 'communication' as compared to the corpus 'language'. Additionally, articles from the latter corpus tend to stress a narrative of human uniqueness. Our results, taken together, do not provide clear evidence for a structural and active promotion of a 'norm of progress', but hint towards historical aftermaths exercising indirect influence and worthy of further study.